(untitled) (Jurnal Ilmu Produksi dan Teknologi Hasil Peternakan, 2026)
Comb honey is honey that remains in the hive and has not undergone extraction, while packaged honey is commercial honey available in the market. This study aimed to analyze the quality of comb honey and packaged honey from the Bojongmurni Beekeeping Area, Bogor District, West Java Indonesia. Each type of honey was analysed directly without any pretreatment, with with 20 replicates for each physical test and three replicates for each chemical test. Physical tests (solubility, turbidity foam, hexagonal pattern, and heating tests) were analyzed descriptively based on effectiveness values (%), whereas chemical tests (moisture content, water insoluble solids, hydroxymethylfurfural (HMF), and diastase enzyme activity) were analyzed descriptively using mean and standard deviation. The physical tests showed high effectiveness (100%) in solubility, heating, and hexagonal tests, while turbidity–foam test values varied: 90±0.22% (fresh honey), 80±0.41% (packaged honey), and 85±0.36% (comb honey). Chemical analyses revealed that HMF (0 mg/kg) and diastase activity (5.18–5.52 DN) met SNI 8664:2024 standards. However, moisture content in packaged (23.8±0.29%) and comb honey (22.2±0.25%), as well as water insoluble solids (0.51%–0.64%), slightly exceeded the SNI limits. Overall, both comb and packaged honey from Bojongmurni Beekeeping Area were confirmed to be pure honey.